2012
DOI: 10.1039/c1sm06085f
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel self-assembled poly(3-acrylamidophenylboronic acid)/poly(2-lactobionamidoethyl methacrylate) hybrid nanoparticles for improving nasal adsorption of insulin

Abstract: It is well-known that the phenylboronic acid derivatives have chemical interactions with sugars. Hence, stable nanoparticles with core-shell structure were formed by the covalent complexation between boronic acid groups of poly(3-acrylamidophenylboronic acid) (pAPBA) and hydroxyl groups of poly (2-lactobionamidoethyl methacrylate) (pLAMA). The image taken by transmission electron microscopy (TEM) shows that the nanoparticles had a size of about 200 nm and were irregular spheres. The methyl thiazolyl tetrazoliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] As well known sugar-sensitive groups, phenylboronic acid (PBA) and its derivatives have been widely applied in glucose-responsive systems. [4][5][6][7][8][9][10][11][12][13][14] Kataoka et al [4] prepared a glucose responsive polymer complex formed between poly(vinyl alcohol) (PVA) and poly(N-vinyl-2-pyrrolidone) with pendant phenylboronic acid moieties [poly(NVP-co-PBA)]. The polymer complex could be transformed from the gel state into the sol state in an aqueous solution of glucose because of the replacement of PVA by glucose, which could facilitate the release of loaded insulin through the complex membrane.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] As well known sugar-sensitive groups, phenylboronic acid (PBA) and its derivatives have been widely applied in glucose-responsive systems. [4][5][6][7][8][9][10][11][12][13][14] Kataoka et al [4] prepared a glucose responsive polymer complex formed between poly(vinyl alcohol) (PVA) and poly(N-vinyl-2-pyrrolidone) with pendant phenylboronic acid moieties [poly(NVP-co-PBA)]. The polymer complex could be transformed from the gel state into the sol state in an aqueous solution of glucose because of the replacement of PVA by glucose, which could facilitate the release of loaded insulin through the complex membrane.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Recently, glucose-responsive polymeric micelles based on PBA-contained amphiphilic block polymers have been reported as promising nanocarriers for delivery of insulin. [9][10][11][12][13][14][15]20] Wang et al [9,20] prepared glucose responsive micelles through selfassembly of poly(ethylene glycol)-block-poly-(acrylic acid-coacrylamidophenylboronic acid) (PEG-b-P(AA-co-APBA)). Insulin was loaded into the micelle core through hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al. developed stable core‐shell nanoparticles for insulin release constructed using poly(3‐acrylamidoPBA) and poly(2‐lactobionamidoethyl methacrylate) . The insulin‐loaded hybrid nanoparticles showed improved nasal adsorption and intracellular transport of insulin.…”
Section: Stimuli‐responsive Release Systemsmentioning
confidence: 99%
“…Scarano et al reported a micelle-based selective drug delivery system based on micelles formed by block copolymers having a catechol terminal decorated with folic acid that had BA moiety. [43] Folic acid enhanced target delivery of the platinum drug-loaded micelles to ovarian cancer cell lines. Jia et al developed a boronate-linked polymeric nanovehicle for a pH-dependent tumor-targeted drug release system 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 consisting of linear poly(ethylene glycol) modified with PBA at the end and hyperbranched poly(5-ethyl-5-hydroxymethyl-1,3dioxan-2-oxo).…”
Section: Nanomaterials For Ddsmentioning
confidence: 99%